Caring for VIPs: Nine principles - Guzman, Jorge A.; Sasidhar, Madhu; Stoller, James K. (Cleveland Clinic Journal of Medicine, 2011)
Caring for very important persons (VIPs), including celebrities and royalty, presents medical, organizational, and administrative challenges, often referred to collectively as the “VIP syndrome.” The situation often pressures the health care team to bend the rules by which they usually practice medicine. Caring for VIP patients requires innovative solutions so that their VIP status does not adversely affect the care they receive. We offer nine guiding principles in caring for VIP patients.